Integrated weed management in soybean (Glycine max) and its residual effect on succeeding wheat (Triticum aestivum)* - IDAPUGANTI, R G; RANA, D S; PACHAURl, DK (The Indian Journal of Agricultural Sciences, 2011)
An experiment on integrated weed management in soybean and its residual effect on succeeding wheat was conducted during 2003-04 at New Delhi. The results showed that 2 hand weedings at 20 and 40 days after sowing or fluchloralin @ 1kg as pre-plant incorporation+ 1hand weeding at 30 days after sowing or mulching with wheat and mustard straw @ 10 tonnes/ha between the rows just after sowing effectively controlled the weeds in soybean and gave similar seed yield of statistical order but superior to the other weed control treatments. Mulching in soybean recorded the highest grain yield of succeeding wheat and lowest was recorded in weedy check of soybean.